Analysis of Student’s Interests in Physical Education Learning Materials Shooting Football through Games - Agustiawan, Dodi; Lanos, Muhsana El Cintami; Handayani, Widya (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine students’ interest in learning physical education in shooting soccer material through games. This research was conducted on fifth grade students at SD Negeri 162 Palembang. Data collection techniques were carried out by means of observation, documentation studies, interviews, and tests. Data analysis techniques were carried out qualitatively and quantitatively. Based on the results of the development it can be concluded: (1) it can be reversion corner teachers; (2) learning has several types of games shooting; (3) this learning will increase children’s interest in taking corner lessons; (4) contribution to the science of education, especially in the field of sports; and (5) make learning more creative and interesting.